Humoral Immune Correlates for Prevention of Postnatal Cytomegalovirus Acquisition. (20th May 2019) - Saccoccio, Frances M; Jenks, Jennifer A; Itell, Hannah L; Li, Shuk Hang; Berry, Madison; Pollara, Justin; Casper, Corey; Gantt, Soren; Permar, Sallie R
Abstract: Background: Development of a cytomegalovirus (CMV) vaccine is a high priority. However, the ability of antibodies to protect against CMV infection is not well characterized. Studies of maternal antibodies in infants offer the potential to identify humoral correlates of protection against postnatal acquisition. Methods: This hypothesis-generating study analyzed 29 Ugandan mother-infant pairs that were followed weekly for CMV acquisition. Seventeen mothers and no infants were infected with human immunodeficiency virus (HIV). We evaluated the association between CMV-specific immunoglobulin G (IgG) responses in mothers at the time of delivery and their infants' CMV status at 6 months of age. We also assessed levels of CMV-specific IgG in infants at 6 weeks of age. CMV-specific IgG responses in the mother-infant pairs were then analyzed on the basis of perinatal HIV exposure. Results: We found similar levels of multiple CMV glycoprotein–specific IgG binding specificities and functions in mothers and infants, irrespective of perinatal HIV exposure or infant CMV status at 6 months of age. However, the glycoprotein B–specific IgG titer, measured by 2 distinct assays, was higher in infants without CMV infection and was moderately associated with delayed CMV acquisition. Conclusions: These data suggest that high levels of glycoprotein B–specific IgG may contribute to the partial protection against postnatal CMV infection afforded by maternal antibodies, and they support the continued inclusion of glycoprotein B antigens in CMV vaccine candidates.